2010
DOI: 10.4317/medoral.15.e322
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of psychiatric drug therapy on oral lichen planus patients with psychiatric disorders

Abstract: http://www.medicinaoral.com/medoralfree01/v15i2/medoralv15i2p322.pdf AbstractObjectives: Current treatments of oral lichen planus are palliative, not curative. Because psychiatric disorders significantly influence the development and severity of oral lichen planus, the use of psychiatric drug therapy may be an adjunct in treatment. The purpose of this study was to determine the efficacy of drug therapy of psychiatric disorders in oral lichen planus. Study design: Our controlled clinical study consisted of fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 9 publications
5
20
0
1
Order By: Relevance
“…Hence, on the basis of the available literature, the reasons for increased prevalence of BMS and OLP in psychiatric patients may be multiple and involve the interaction of biological and psychological systems. Thus, Delavarian et al (20) suggested the use of a combination of psychotherapy and conventional treatment in OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, on the basis of the available literature, the reasons for increased prevalence of BMS and OLP in psychiatric patients may be multiple and involve the interaction of biological and psychological systems. Thus, Delavarian et al (20) suggested the use of a combination of psychotherapy and conventional treatment in OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have been done for the evaluation of the relationship OLP and psychiatric disorders. These studies used various psychiatric questionnaires, but any treatment intervention has not been used but in our study, after diagnosis of psychiatric disorders by psychiatric interview, we treated these disorders with psychiatric pharmacotherapy (Delavarian 2010). Among different studies, some found a positive correlation between OLP and psychiatric disorders; however other studies did not establish such a relationship.…”
Section: Psychiatric Comorbidity and Oral Lichen Planusmentioning
confidence: 96%
“…In another study, combination of amitriptyline, ketokonazole, and clobetasole in mouthwash form was useful in OLP patients (Javadzadeh 2008). For the first time, in one study, we evaluated the effects of concurrent routine treatment of OLP lesions with topical corticosteroid and psychiatric therapy of patients with psychiatric disorders (Delavarian 2010) .…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations